Development of Information Service Modul to Enhance Meaning of Life: A Study on Minangkabau Adolescents - Permatasari, Yuli; Nirwana, Herman; Usman, Hanifah (Journal of Educational, Health and Community Psychology, 2024)
This study examined the development of informational service materials aimed at enhancing the meaning of life among Minangkabau ethnic students in secondary schools. "Meaning of life" is a psychological concept referring to an individual's sense of purpose, significance, and life satisfaction. The research employed a Research and Development (R&D) approach using the ADDIE model, and data analysis was conducted using the Wilcoxon Signed Rank Test. The results indicate that the developed informational service materials are valid in terms of content and design, practical, and effective in improving the students' meaning of life. These materials were tested on a small group using a limited trial method, which demonstrated an increase in the meaning of life before and after the informational service was provided. The implications of this study suggest that the use of informational services to enhance the meaning of life can be effectively applied to students, as it has a positive psychological impact.